Contributing factors and main agents affecting building defects in the coastal environmental of Malaysia: a qualitative study / Suriani Ngah Abdul Wahab ... [et al.] - Ngah Abdul Wahab, Suriani; Rusli, NorFatihah; Hashim, Hasnan; Radin Mohd Mokhtar, Munirah; Nur’aini, Ratna Dewi (2022)
Nowadays, there are many different types of buildings that need to be taken care of, including residential, office, commercial, and other types of buildings. Certainly, a variety of environmental conditions, such as those found on the shore or in a coastal area, play a part and contribute to building defects. In terms of aesthetics and ecology, the majority of people always feel that building near the sea is one of the most comfortable places to live. However, there are certain weaknesses to owning a home in a seaside area, including those defects can emerge more quickly than in a non-coastal environment. Therefore, the objectives of this study were to identify the main agents that contributed to the defects and offered coastal defect prevention to limit future difficulties. There is a need for a proper decision to solve this situation. Literature review, questionnaires and observation were used to obtain data for this study and four case studies have been performed in this research. Saltwater and rainwater, strong waves, and driving rain (monsoon season) were among the most frequent cause of defects in coastal residential buildings. Corrosion, rot on structures, and cracks as a result of erosion are examples of architectural problems. As a result, while performing regular inspection and maintenance on each structure, selecting the appropriate materials can significantly minimise or reduce damages and could improve the building condition in the future.